Automatización del sistema de bombeo de agua potable para el recinto Santa Marianita del Cantón Puerto Quito. - Chicaiza Riofrio, Alex Hernan (2023)
The objective of this project is the development of an automated drinking water pumping system taking the Santa Marianita Campus of the Puerto Quito Canton as a case study. The Santa Marianita Campus lacks a control system for the power system and the monitoring of the water level in the 403 reception tank. The on-site visit was carried out to gather information and, based on that, propose a prototype that meets the needs of the place, the water intake for pumping to the reception tank is located 239 km apart and the water extraction is from a 106 deep well using a 5HP submersible water pump.